Analysis of Financial Statements to Measure Performance at PT. Kino Indonesia, Tbk 2015-2019 - Yuli Fitriyani; Mufrida Zein; Radna Nurmalina; Mega Putri Diyani (International Journal of Research in Vocational Studies (IJRVOCAS), 2022)
This study aims to analyze the financial performance of PT. Kino Indonesia Tbk from 2015-2019 by calculating financial ratios. The type of data used is quantitative data. The data collection methods used were documentation and literature study which were analyzed using financial ratios, namely liquidity ratios, solvency ratios, and profitability ratios. The results show that the liquidity ratio, namely the current ratio, is not yet effective because the company has not been able to pay current debts using assets, while the quick ratio is declared effective because the company is able to pay short-term debt with current assets without taking inventory into account. The solvency ratio, namely the debt to asset ratio, is declared ineffective because the company has not been able to pay all of its debts using assets and the debt to equity ratio is effective because the company is able to pay all its debts using all equity. Profitability ratios, namely return on assets and return on equity, fluctuate every year because the company has not been able to obtain maximum profit.